Genetic expression of enzyme I activity of the phosphoenolpyruvate:sugar phosphotransferase system in ptsHI deletion strains of Salmonella typhimurium. - Chin, A M (1987)
Mutants expressing a novel enzyme I of the phosphoenolpyruvate:sugar phosphotransferase system, termed enzyme I, were isolated from strains of Salmonella typhimurium which were deleted for the HPr and enzyme I structural genes. The mutations lay in a newly defined gene, termed ptsJ, which mapped on the S. typhimurium chromosome between the ptsHI operon and the cysA gene.